[Rezension von: Yijiang Zhong, The origin of modern Shinto in Japan] - Andreeva, Anna (Entangled Religions, 2016)
This contribution offers a review ofYoshihiro Nikaido: Asian Folk Religion and Cultural InteractionTaipei: National Taiwan University Press, 2015.Göttingen:V&R unipress, 2015. 230 pages, with numerous figures.hardcover € [D] 49,99/€ [A] 51,40, ISBN 978-3-8471-0485-8